The reaction of CIMMYT durum wheat genotypes to Fusarium pseudograminearum at seedling and adult plant stages - Yilmaz, Olgaç Doğu; Karakaya, Aziz; Erginbas-Orakci, Gul; Aydogan, Sinan; Ammar, Karim; Dababat, Abdelfattah A. (Cambridge University Press, 2023)
Fusarium pseudograminearum is one of the important crown rot agents that reduces the quality and quantity of wheat plants. The pathogen is common in the world and 10-35% yield losses due to disease have been reported. Identifying resistant durum wheat genotypes is the best approach to control the disease due to the limited control options available. Currently, there are only a few genotypes available with partial resistance to Fusarium crown rot globally. In this study, a total of 199 durum wheat genotypes provided by the International Wheat and Maize Improvement Center (CIMMYT), Mexico, and five control genotypes were tested for their resistance reactions to F. pseudograminearum under both growth room and greenhouse conditions. Out of the 199 genotypes tested under growth room conditions; 15, 20, 134 and 30 genotypes exhibited resistant, moderately resistant, moderately susceptible and susceptible reactions, respectively. Under greenhouse conditions; 19, 16, 121 and 43 genotypes were found resistant, moderately resistant, moderately susceptible and susceptible, respectively. Two durum wheat genotypes (# 84 and # 197, CIMMYT genotype numbers 7409071 and 7410562) showed seedling and adult plant resistance to F. pseudograminearum. The newly identified resistant genotypes for crown rot caused by F. pseudograminearum seem promising for breeding programmes, especially these two lines which showed resistance at both seedling and adult plant stages.